Pengaruh Tanggung Jawab Guru Terhadap Motivasi Belajar Siswa SD Negeri 101824 Durin Simbelang Kecamatan Pancur Batu Tahun Pembelajaran 2022/2023 - Desi Natalia Br Ginting; Reflina Sinaga; Dyan Wulan Sari HS; Rumiris Lumban Gaol; Darinda S. Tanjung (Journal on Education, 2023)
This study aims to determine the effect of teacher responsibility on student learning motivation at SD Negeri 101824 Durin Simbelang in the 2022/2023 school year. In this study using quantitative methods, the population of this study was all classes I-VI SD 101824 Durin Simbelang which amounted to 159 students. sampling using random sampling is said to be simple because it takes sample members from the population randomly and the samples used are students of SD Negeri 101824 Durin Simbelang which amounted to 40 students. The results of this study indicate that student learning motivation with teacher responsibility is included in the very good category with an average of 86, with the correlation test results of 0.904 which means rcount (0.904) ≥ rtable (0.312) then Ha is accepted. So there is a very strong influence between the use of teacher responsibility on student learning motivation at SD Negeri 101824 Durin Simbelang. It can be seen from the results of the T-test research where tcount ≥ ttable, namely 13.049 ≥ 0.312 so it can be stated that Ha is accepted. This shows that there is a significant positive effect of teacher responsibility on student learning motivation at SD Negeri 101824 Durin Simbelang in the 2022/2023 school year.